Socio-Economic Determinants of Smallholder Farmers' Adoption of Climate-Smart Agricultural Practices in Rice-Farming Communities - Abdul Wahib Muhaimin; Dina Novia Priminingtyas; Lis M. Yapanto (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Climate-Smart Agricultural Practices (CSAPs) offer a promising pathway for enhancing agricultural productivity, building resilience to climate change, and reducing greenhouse gas emissions in smallholder rice-farming systems. Despite their potential, adoption rates remain persistently low across many developing regions. This study examines the socio-economic determinants influencing smallholder farmers' adoption of CSAPs in rice-farming communities. Using survey data collected from 320 rice-farming households, a binary logistic regression model was employed to identify key factors affecting adoption decisions. The results reveal that farmer education level, household size, farm size, access to extension services, membership in farmer organizations, access to credit, and perception of climate change are significant determinants of CSAP adoption. Specifically, farmers with higher education levels (p < 0.01), larger farm sizes (p < 0.05), and access to extension services (p < 0.01) were significantly more likely to adopt climate-smart practices. Conversely, age of household head showed a negative relationship with adoption, suggesting that younger farmers are more inclined to adopt innovative practices. These findings underscore the need for targeted policy interventions that strengthen agricultural extension systems, improve access to credit, and enhance climate information dissemination to promote wider adoption of CSAPs among rice-farming communities. Keywords: climate-smart agriculture; smallholder farmers; rice farming; adoption determinants; socio-economic factors; agricultural extension